Examining digital marketing's role in boosting Songket Weaver MSMEs' income in Ungga and Sukarara Villages - Aprilani, Triana Lidona; Fathurrahman, Fathurrahman; Andriyani, Yanti; Cahayani, Mimi; Saksono, Herie; Indarti, Dian Martha; Putra, Imam Radianto Anwar Setia (Central Community Development Journal, 2025)
This study investigates how digital marketing shapes the income of Micro, Small, and Medium Enterprises (MSMEs) engaged in songket weaving in Ungga and Sukarara Villages in Central Lombok Regency, West Nusa Tenggara Province, Indonesia. Songket weaving is a culturally embedded craft, but its market prospects increasingly depend on visibility and engagement in digital channels. Using a quantitative design, data were collected from 100 songket weaver MSMEs through structured questionnaires and analyzed using partial least squares-structural equation modeling (PLS-SEM). Digital marketing is conceptualized through five dimensions, accessibility, interactivity, entertainment, trust, and informativeness, while MSME income is measured by monthly revenue and profit. The measurement model demonstrated satisfactory convergent and discriminant validity, as well as high reliability across all indicators. The structural model shows that digital marketing has a strong and statistically significant positive effect on MSME income (β = 0.747; p < 0.001), explaining 55.8% of the variance (R² = 0.558) with high predictive relevance (Q² = 0.671). These findings confirm that more intensive and higher-quality use of digital channels is associated with higher income for the songket weavers. The study concludes that targeted interventions, such as digital marketing training, content creation support, and facilitation of social media and marketplace usage, are critical to enhancing the competitiveness, resilience, and livelihood outcomes of traditional craft-based MSMEs in peripheral tourism regions like Central Lombok. This study contributes to the MSME and digital transformation literature by providing destination-specific evidence from a craft cluster in an emerging economy context and offering an empirically grounded basis for designing local government and development agency programs for the digital empowerment of artisans.